1991
DOI: 10.1093/nar/19.24.6691
|View full text |Cite
|
Sign up to set email alerts
|

Site-specific hydrolysis and alcoholysis of human immunodeficiency virus DNa termini mediated by the viral integrase protein

Abstract: Before integration of the human immunodeficiency virus (HIV) DNA, two nucleotides are removed from the 3' ends of the viral DNA by the integrase (IN) protein. We studied the chemistry of this reaction, and found that IN mediates site-specific hydrolysis of a phosphodiester bond, resulting in release of a dinucleotide. A class of alcohols (including glycerol, 1,2-propanediol, but not 1,3-propanediol) can also act as nucleophile in this reaction, and likewise the alcoholic amino acids L-serine and L-threonine ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
129
1

Year Published

1992
1992
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(134 citation statements)
references
References 26 publications
4
129
1
Order By: Relevance
“…The 3=-processing substrates, which modeled the HIV-1 U5 vDNA end, were labeled by incorporating radionuclide T at the plus-strand terminus, allowing reactions to be monitored through formation of labeled pGT OH cleavage product in denaturing polyacrylamide gels (Fig. 1A and B) (41,121). IN WT activity was defined as the percent substrate converted to product, and mutant activities were quantified relative to IN WT values ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The 3=-processing substrates, which modeled the HIV-1 U5 vDNA end, were labeled by incorporating radionuclide T at the plus-strand terminus, allowing reactions to be monitored through formation of labeled pGT OH cleavage product in denaturing polyacrylamide gels (Fig. 1A and B) (41,121). IN WT activity was defined as the percent substrate converted to product, and mutant activities were quantified relative to IN WT values ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It seems possible that the carboxylate groups of the invariant D and E residues of IN may complex with metal to establish a similar DNA-enzyme intermediate. Cleavage of DNA strands may then be accomplished by nucleophilic attack via a hydroxyl group of an amino acid side chain on the protein (18,21), the 3' OH of processed LTR end (12,25), or a water molecule (12,34). We hypothesize that the invariant acidic residues in the D,D(35)E region are critical for metal binding and positioning of the DNA substrate for nucleophilic attack.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the biochemical activities of deletion derivatives of integrase has shown that this domain alone can promote the disintegration reaction, demonstrating that it is sufficient for catalysis of polynucleotidyl transfer (Bushman et al, 1993). However, the 3' processing and DNA strand transfer reactions require in addition both the N-and C-terminal parts of the protein (Drelich et al, 1992;Bushman et al, 1993 (Engelman et al, 1991;Vink et al, 1991b). The reactions contained the same protein reactants as in panel A.…”
Section: Introductionmentioning
confidence: 99%